Early anthropogenic use of hematite on Aurignacian ivory personal ornaments from Hohle Fels and Vogelherd caves, Germany. Issue 150 (January 2021) - Velliky, Elizabeth C.; Schmidt, Patrick; Bellot-Gurlet, Ludovic; Wolf, Sibylle; Conard, Nicholas J.
Abstract: The Aurignacian (ca. 43–35 ka) of southwestern Germany is well known for yielding some of the oldest artifacts related to symbolic behaviors, including examples of figurative art, musical instruments, and personal ornaments. Another aspect of these behaviors is the presence of numerous pieces of iron oxide (ocher); however, these are comparatively understudied, likely owing to the lack of painted artifacts from this region and time period. Several Aurignacian-aged carved ivory personal ornaments from the sites of Hohle Fels and Vogelherd contain traces of what appear to be red ocher residues. We analyzed these beads using a combination of macroanalytical and microanalytical methods, including scanning electron microscopy equipped with energy dispersive spectroscopy and Raman spectroscopy. We found that the residue is composed of the iron oxide mineral hematite (Fe2 O3 ). Further analyses on associated archaeological sediments by X-ray diffraction revealed the absence of hematite and other iron oxide mineral phases, suggesting that the hematite residues were intentionally applied to the ivory personal ornaments by human agents. These findings have important implications as they represent evidence for the direct application of ocher on portable symbolic objects by early Homo sapiens in Europe. Furthermore, our results reveal shared behavioral practices from two key Aurignacian sites maintained over several millennia and illuminate aspects of pigment use and symbolic practices during a pivotal time in the cultural evolution of humans. Highlights: Our results confirm that red colorants on Aurignacian-aged ivory beads are the mineral hematite (Fe2 O3 ) or ocher. No hematite or other iron oxide phases were found in associated sediments; the ocher was indeed anthropogenically applied. Ocher was found on beads during all stages of production, suggesting complex behavioral practices. This is the first study confirming the presence of anthropogenic ocher on Aurignacian-aged ivory beads from Europe. This study provides new insight into how ocher was used by some of the earliest Homo sapiens in Europe.